Acute Levodopa Challenge Test in Patients with de novo Parkinson's Disease: Data from the DeNoPa Cohort. Issue 5 (30th June 2017) - Schade, Sebastian; Sixel‐Döring, Friederike; Ebentheuer, Jens; Schulz, Xenia; Trenkwalder, Claudia; Mollenhauer, Brit
Abstract: Background: The precise clinical diagnosis of Parkinson's disease (PD) can be difficult in the early stages. Diagnostic criteria include the response of key motor features to levodopa as a supportive prospective criterion. Data are sparse on the diagnostic value of the acute levodopa challenge test (LDCT) in patients with de novo PD. The objective of this study was to validate the LDCT as a tool in the early clinical diagnosis of PD. Methods: We performed the standardized LDCT with 250 mg levodopa in the prospective longitudinal cohort study "DeNoPa, " comprising 159 patients with de novo PD, and carried out longitudinal clinical follow‐up for 24 months. Motor assessments at baseline using the motor part (part III) of the Unified Parkinson's Disease Rating Scale before and 1 hr after drug administration were documented. The optimal cutoff score on the LDCT was calculated using the Youden index. Results: Clinical reassessment of 144 patients who returned for follow‐up confirmed the diagnosis of PD in 120 patients (83%). In 24 patients (17%), the initial diagnoses were revised and classified as other neurologic disorders. The optimal cutoff at 33% improvement of motor symptoms on the part 3 of the Unified Parkinson's Disease Rating Scale during the LDCT reached a sensitivity of 70% a specificity of 71%. The positive and negative predictive values were 92% and 32%, respectively. Sensitivity (91%), specificity (79%), and positive/negative (96%/63%) predictive values improved with the addition of further clinical information (urinary incontinence, fainting, asymmetric tremor, and amount of further drug‐intake). Conclusions: The LDCT is a reliable tool in the early diagnosis of PD. The accuracy of this test can be further improved by additional, easy‐to‐acquire clinical information provided by patients. © 2017 International Parkinson and Movement Disorder Society.